Nonalcoholic Fatty Liver Disease as a Potential Risk Factor for Cardiovascular Disease in Patients with Type 2 Diabetes: A Prospective Cohort Study - Mohammad Dehghani Firouzabadi; Amirhossein Poopak; Ali Sheikhy; Fatemeh Dehghani Firouzabadi; Fatemeh Moosaie; Soghra Rabizadeh; Sara Momtazmanesh; Manouchehr Nakhjavani; Alireza Esteghamati (International Journal of Endocrinology)
Background and Objectives. Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disorder in western countries. Although the etiology of NAFLD is unknown, insulin resistance is a key mechanism of lipid deposition in hepatocytes leading to steatosis and potentially steatohepatitis in patients with diabetes. These factors accelerate the progression of atherosclerosis and development of cardiovascular diseases (CVD). Methods and Results. In this prospective cohort study, 1197 patients with type 2 diabetes (T2D) were divided into two groups (360 patients with NAFLD and 847 without NAFLD) and were followed for a median of 5 years for the incidence of CVD. Cox regression analysis was used to assess the association between NAFLD, liver enzyme level, aspartate aminotransferase to platelet ratio index (APRI), and the incidence risk of CVD and its subgroups (i.e., myocardial infarction, chronic heart disease, coronary artery bypass grafting, and percutaneous coronary intervention). There was a significant positive association between CVD incidence and NAFLD (HR = 1.488, 95% CI = 1.041–2.124, p value = 0.029). Although patients with NAFLD had higher levels of ALT and AST levels (p value = <0.001), there was no significant association between liver enzymes and the incidence risk of CVD when adjusted for different variables. Furthermore, NAFLD was associated with NAFLD APRI Q (2), APRI Q (3), and APRIQ (4) (1.365 (1.046–1.781), 1.623 (1.234–2.135), and 3.373 (2.509–4.536)), respectively. Conclusion. NAFLD increased the incidence risk of CVD in T2D. However, there was no association between liver enzymes (ALT, AST, ALK-P, and GGT) and a higher incidence risk of CVD in T2D when adjusted for confounding variables.